Enhancing Halal Sustainability through Family Takaful Products Based on the Maqasid Shari’ah Framework - Ismail, Norhissyam; Fisol, Wan Nazjmi Mohamed (Prosiding Seminar; 2019: 2019 International Conference of Interdisciplinary Sciences, 2020)
Takaful is growing fast day by days. Other than it can develop the industry of Takaful itself, the main reason by introducing the takaful insurance is to offer or provide an alternative to all Muslims’ needs in protection product . Thus, similar to the conventional insurance, it is to provide the element of protection and indemnity to both individual and corporate bodies against loss or hazards to their selves or wealth but in line with the Maqasid Shari’ah Principles. Hence, the objective of the study has been evaluated the family takaful product which based on the Maqasid Shari’ah framework due to the five preservations or protections (Protection of Religion, Protection of Life, Protection of Intellect, Protection of Progeny and Protection of wealth). Most of the products offered in takaful institutions are in line with the Maqasid Shari’ah perspective as sustainable of financial planning which bring to the social well-being and impartiality for the public interest ( maslahah ) by taking into consideration of five preservation, namely the preservation of religion ( al-ddin ), the preservation of life ( al-nafs ), the preservation of intellect ( al- ‟ aql ), the preservation of progeny ( al-nasl ) and the preservation of wealth ( al-mal ). Therefore, it is an important not only in developing takaful as a part of industry growing but then beyond than that to fulfill the needs of Muslim as well for all the others as well as enhancing halal sustainability through takaful products development.